Визначення збитків від відхилень показників якості електроенергії в електроприводах сільськогосподарських машин - Синявський, О. Ю.; Савченко, В. В. (Енергетика і автоматика, 2017)
DETERMINATION OF LOSS FROM deviation of the Power Quality in the electric drive of AGRICULTURAL MACHINERY A. Sinyavsky, V. Savchenko Deviations from power quality parameters normalized values leads to negative consequences - put losses from breach of the normal course of technological processes, reduced service life of electrical equipment, rising costs and the loss of electricity emergencies arise. The most widely used cost estimates of the quality of electricity supply. The greatest difficulty is the loss calculation of the consumer, as in this case must take into account the technological features of production. The loss of consumer consists of two parts: the electrical and technological component. Electrical component based on job descriptions and performance of the system is measurable. Indicators technological component dependencies installed approximation based on empirical data. The purpose of research - development of methods for determining losses for power quality indicators deviation from the nominal values of electric drives in agricultural machines. Materials and methods of research. The research results SP Kucera reflected in the guidelines VIESH where given technological parameters depending on the specifications of electrical installations. This information allows you to change depending on technological parameters for voltage deviations. These recommendations VIESH models designed for electrical installations and that produced in the 70’s of last century and now almost does not apply. They are defined only for large livestock and poultry farms and complexes. Conducted research only damage from exposure to voltage fluctuation. In addition, some are not, depending adequately reflect the real processes occurring in electric drives of agricultural machinery. So use this method now can not. In this connection there is a need to develop new methods for determining the loss of power quality deviation indicators that would be consistent with the realities of modern agriculture, modern system of machines and the results of research carried out in recent years. Results. Dimensions losses inflicted to agricultural production by sudden interruptions in the supply of electricity, time and duration are determined off, the phase of the production cycle, climatic conditions and depend on the adopted technology and productivity of animals and plant yield. The technological component damage due to power electric power low quality, includes losses: - From lost productivity of working machines; - From reduced productivity of livestock and poultry; - From disease, death of livestock and poultry and their premature rejection; - From lower yields and loss of crops covered ground; - The growth of losses during storage; - Because of the deterioration of raw materials and finished products; - Due to reduced yields of quality. The dependence of the external factor of power quality index, making it possible to receive analytical performance changes depending on animal and crop yields rejecting the corresponding figure of power quality from the nominal value and determine the appropriate technical losses. Conclusions Established that at lower voltage 20% increase in weight of pigs decreased by 5.8% calves - by 2.1%, milk yield of cows - by 0.5%, egg laying chickens - at 0.65% with increasing feed intake for calves 4 , 8% and pigs - by 13.4%. Yields vegetable greenhouses in winter decreased with 4.6% and the preservation of potatoes in the potato - by 1.1%. When the voltage of technological losses smaller than at its depression. The current frequency deviation of current network technology does not cause significant damage (they do not exceed 0.2%).